2019
DOI: 10.1177/1354816619834482
|View full text |Cite
|
Sign up to set email alerts
|

The economic value and determinants of tourists’ counterfeit purchases: The case of Hong Kong

Abstract: Counterfeiting of fashion brands is a multi-billion dollar industry with an increasing number of goods being counterfeited. This research takes a demand-side approach to measuring counterfeiting activity among tourists in Hong Kong. Non-deceptive counterfeit purchases by tourists in Hong Kong amount to US$761.32 million per year. Tourists’ decision of whether to purchase counterfeit goods depended on a mix of extrinsic and intrinsic factors including psychometric variables, trip-related characteristics, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Usually, consumers prevent themselves from buying counterfeit luxury, and these customers are categorized as 'right motives' buyers (Purwanto et al, 2019). However, sometimes, sellers are going to deceit customers by selling counterfeit luxury items (Pratt & Zeng, 2019). Besides, when the consumer is eager to purchase counterfeit luxury goods, it is considered as a non-deceptive counterfeit purchasing (Chiu & Leng, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Usually, consumers prevent themselves from buying counterfeit luxury, and these customers are categorized as 'right motives' buyers (Purwanto et al, 2019). However, sometimes, sellers are going to deceit customers by selling counterfeit luxury items (Pratt & Zeng, 2019). Besides, when the consumer is eager to purchase counterfeit luxury goods, it is considered as a non-deceptive counterfeit purchasing (Chiu & Leng, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This tends to be critical given the illegal nature of counterfeiting. It is argued that situational factors related to leisure and recreation such as holiday mood can also influence counterfeit purchases (Pratt & Zeng, 2019); their influence, however, is likely to be transient. The mood can even suppress the deterring effect of consumers' attitudinal beliefs, such as respect for lawfulness on counterfeit purchases.…”
Section: Synthesizing Research Domainsmentioning
confidence: 99%
“…However, most studies have suggested that age doesn't influence CF purchase intention (Bian & Mountinho, 2009;Hamlin et al, 2012;Poddar et al, 2012, Pratt & Zeng, 2019.…”
Section: The Impact Of Age On Customer Intention To Purchase Counterf...mentioning
confidence: 99%
“…Almost all of the extracted research that have investigated gender's influence on CF purchase intention (Bian et al, 2016;Norum & Cuno, 2011;Poddar et al, 2012;Pratt & Zeng, 2019;Randhawa et al, 2015;Riquelme et al, 2012;Swami et al, 2009) and there was no evidence that gender has any influence on CF purchase intention. For example, Norum & Cuno (2011) revealed that consumer intention toward counterfeit brands was not significantly affected by gender, However, Hamelin et al, (2013) tested intention to buy counterfeit brands in 3 main categories of goods: clothing, cosmetics, and cellular phones, and customer demographics have been examined in an attempt to profile buyers who are likely to consider purchasing (or avoiding) counterfeit products.…”
Section: The Impact Of Gender On Intention To Buy Counterfeit Goodsmentioning
confidence: 99%
See 1 more Smart Citation